Strategi Transformasi Digital dalam Penguatan Motivasi Belajar Mahasiswa di Perguruan Tinggi Keagamaan Islam - Jamarudin Jamarudin; Akhmad Shunhaji; Ahmad Zain Sarnoto (At Tadbir: Islamic Education Management Journal, 2026)
Digital transformation has become one of the strategies adopted by higher education institutions to improve the quality of learning. However, research examining digital transformation as an institutional strategy to support student motivation, particularly in faith-based higher education institutions, remains relatively limited. This study aims to analyse digital transformation strategies and identify the challenges faced in supporting student learning motivation. The research employs a qualitative approach using a case study design at the Faculty of Da’wah and Communication Sciences, PTIQ University, Jakarta. Data were collected through interviews, observations and documentation, and subsequently analysed using the interactive model developed by Miles, Huberman and Saldaña. The findings indicate that digital transformation strategies are implemented through curriculum updates, the optimisation of digital learning platforms, and the strengthening of lecturers’ and students’ digital competencies via ongoing training and mentoring. These strategies support the creation of a more flexible and interactive learning process and are seen as contributing to an increase in students’ motivation to learn. The main challenges faced include the uneven level of lecturers’ digital competencies, limitations in technological infrastructure, and institutional capacity. This study makes an empirical contribution by demonstrating that the implementation of digital transformation requires an integrated approach combining curriculum reform, the enhancement of digital skills, and institutional support to foster students’ motivation to learn